Perbedaan Pengetahuan dan Perilaku Mahasiswa Kesehatan Mulut Kelas 5-6 (UKGS dan NON-UKGS) - Sucy Hasfya; Idamawati Nababan; Suci Erawati (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; children aged 6-12 years are prone to age transition, due to changing the age of teeth with permanent teeth. Aim; know the level of knowledge and behavior of dental health and oral among elementary school students in grades 5 and 6 who have a dental health clinic and do not yet have a dental health clinic. Method; is an analytic survey research with a cross-sectional design. Analysis test using chi-square. Result; shows the level of knowledge of dental and oral health of grade 5 and 6 elementary school students who do not have a dental clinic get a value of p = 0.023. The difference in the behavior of maintaining oral health among grade 5 and 6 elementary school students who did not have a dental health clinic was p = 0.006. Conclusion; that there are differences in the level of knowledge and behavior of dental and oral health between grade 5 and 6 SD students who have a dental health clinic and those who do not have a dental health clinic